Children's perception on the gender role content of Philippine television programs. - Brillo, Kharla Mae D.
This study aimed to find out the gender role portrayals in Philippine televisions programs. The narratives of elementary students regarding their perceptions of two primetime shows, Honesto and Got To Believe were analyzed. The sample consisted of twenty-one (21) respondents that have passed the criteria prior to the interview., The analysis revealed that male characters are perceived to be capable of acquiring a higher level of education and occupation; are generally richer; engage in physically demanding activities; usually care less of how they look and are socially inhibited. Conversely, female characters are perceived to engage in domestic chores; particularly lighter activities; are more creative; are more sociable; are commonly concerned of their physical appearance; and are often victims of maltreatment.